An Unexpected Hepatic Hydrothorax After a Successful Kasai Portoenterostomy: A Case Report - Giulia Ranucci; Fabiola Di Dato; Daniela Liccardo; Marco Spada; Giuseppe Maggiore; Raffaele Iorio (Frontiers Media S.A., 2021)
Hepatic hydrothorax (HH) represents a rare complication of portal hypertension among adult cirrhotic patients. Here, we describe a pediatric case of HH, observed in a biliary atresia infant. The child presented with recurrent right-sided pleural effusion, after a successful Kasai portoenterostomy with restoration of bile flow and without overt signs of hepatic failure. Recurrence of HH led the patient to liver transplant despite a low pediatric end-stage liver disease value. Although rare, HH can also occur in children and should be suspected in patients with portal hypertension and respiratory distress. HH may be an indication for liver transplantation.